Evaluation of Water Resources Utilization Efficiency in Guangdong Province Based on the DEA–Malmquist Model - Cheng, Lifen; Song, Song; Xie, Yufeng (Frontiers in Environmental Science, 2022)
Abstract: Water is significant resource supporting socio-economic growth and maintaining environment health. The water utilization efficiency (WUE) reflected the intensity and potential of water use and development. Moreover, improving water-use efficiency is conducive to the sustainable development of the economic–social–ecological system in regional and global scale. In this study, we examined the temporal and spatial trends of water resources utilization efficiency in highly developed Guangdong Province based on data envelopment analysis (DEA) model and Malmquist index, trying to evaluate and predict the water resources utilization status in prefecture-level cities from the input–output perspective. The results showed that, the WUE in Guangdong Province in 2012–2018 was on fluctuated upward trend, although the utilization efficiency had not reached the DEA efficiency; spatially, the WUE in Guangdong Province was relatively high in the Pearl River Delta and the surrounding cities, but low in Western Guangdong region; in the perspective of efficiency decomposition factors, technological change was the most pervasive driving forces of the WUE. Pearl River Delta and Northern Guangdong made progress in productivity due to the advantages of scale expansion benefit. Western Guangdong achieved improvement in all-over parameters and made largest growth in WUE, while Western Guangdong were basically profited from organizational management during the study period; the prediction analysis revealed a continuous increase in the WUE in Guangdong Province during 2019-2025 with an average annual growth rate about 0.6%, benefiting mainly from the technological innovation and secondly from management renewal, while scale expansion benefit tends to decline. Furthermore, spatial heterogeneity exhibits a decreasing tendency in the future owing to the rapid WUE increase in the Western and Eastern Guangdong. Achieving a balance between economic growing and water resource protection, and promoting the sustainable development of nature-economy-society compound system by enhancing water use efficiency is of uppermost priority in Guangdong.